2023
DOI: 10.1021/accountsmr.2c00221
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Comparison of Mildly Acidic versus Alkaline Zinc Batteries

Abstract: Metrics & MoreArticle Recommendations * sı Supporting InformationA queous rechargeable batteries are cost-effective, easy to fabricate, and safe, deliver high energy output, and employ stable water-based electrolytes compared to organicbased lithium-ion batteries (LIBs). Aqueous Zn electrochemistry, specifically, has attracted researchers since the 1830s. Metallic Zn is a nearly ideal anode owing to its low cost (ca. 2 USD kg −1 ), existing supply chain, environmental benignity, relative safety, and high stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The traditional aqueous neutral composition for ZABs is based on the Leclanché battery electrolyte system, whereas ZIBs employ ZnSO 4 or Zn(CF 3 SO 3 ) 2 . A near-neutral electrolyte decreases Zn solubility, which minimizes electrode carbonation and Zn dendrite growth [19,94].…”
Section: Zinc-air Batteries (Zabs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional aqueous neutral composition for ZABs is based on the Leclanché battery electrolyte system, whereas ZIBs employ ZnSO 4 or Zn(CF 3 SO 3 ) 2 . A near-neutral electrolyte decreases Zn solubility, which minimizes electrode carbonation and Zn dendrite growth [19,94].…”
Section: Zinc-air Batteries (Zabs)mentioning
confidence: 99%
“…These technologies are crucial for large-scale applications like EVs, grid management, and mobile electronics [12]. However, they face challenges in efficiency, durability, corrosion, and cycle life, making them uncompetitive for widespread practical applications [12,13,[16][17][18][19]. Moreover, metal anodes and multivalent charge carrier ions can improve energy density, but their limitations and lack of transferrable knowledge from LIB research make them unsuitable for ordinary use [14].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noticed that both Na + and H + coexist in aqueous Na-based electrolytes. The presence of H + due to the slight ionization of water results in H + reduction at the anode together with the Na + reduction during the charging process. This leads to difficulties in the control of reactions and a series of side reactions at the interface between the anode and the aqueous electrolyte, resulting in anode corrosion and bubbles, which seriously impact the electrochemical stability and cause the risk of battery explosion.…”
Section: Introductionmentioning
confidence: 99%
“…16−22 In the absence of zinc, MnO 2 cathodes mixed with CuO and Bi 2 O 3 could be successfully cycled several thousand times without significant loss of delivered capacity; 20,23−27 however, the delivered capacity is derived from accessing available MnO 2 , Cu, and Bi 2 O 3 capacity. 5 There is significant ongoing research focused on understanding the redox mechanism of MnO 2 cathodes in rechargeable Zn/MnO 2 batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical energy storage is essential for the efficient grid integration of renewable energy systems. Rechargeable alkaline Zn/MnO 2 batteries present an attractive option for large-scale electrical energy storage because of their low cost, nontoxicity, and high energy density. In primary Zn/MnO 2 batteries, the rechargeability of MnO 2 cathodes is hindered by the formation of irreversible discharge reaction products. ,, It has been shown that the rechargeability of MnO 2 cathodes in alkaline Zn/MnO 2 batteries could be substantially improved either by restricting the depth of discharge ,, or by using MnO 2 cathodes modified with Cu and Bi additives. In the absence of zinc, MnO 2 cathodes mixed with CuO and Bi 2 O 3 could be successfully cycled several thousand times without significant loss of delivered capacity; , however, the delivered capacity is derived from accessing available MnO 2 , Cu, and Bi 2 O 3 capacity . There is significant ongoing research focused on understanding the redox mechanism of MnO 2 cathodes in rechargeable Zn/MnO 2 batteries.…”
Section: Introductionmentioning
confidence: 99%